Cre-loxP Reporter Mouse Reveals Stochastic Activity of the Foxp3 Promoter - Bittner-Eddy, Peter D.; Fischer, Lori A.; Costalonga, Massimo (Frontiers in Immunology, 2019)
Mouse models that combine specific loxP-flanked gene sequences with Cre recombinase expressed from cell-regulated promoters have become important tools to investigate gene function. Critically however, expression of Cre recombinase may not always be restricted to the target cell or tissue of interest due to promiscuous activity of the driving promoter. Expression of Cre recombinase and, by extension, excision of the loxP-flanked gene may occur in non-target cells and may not be readily apparent. Here we report on the fidelity of Cre recombinase expressed from the il17a or Foxp3 promoters by combining them with a constitutively expressed floxed-stopped tdTomato reporter gene. Foxp3-driven Cre recombinase in F1 mice induced tdTomato red fluorescent protein in Treg cells but also in a range of other immune cells. Frequency of tdTomato expression was variable but positively correlated (p < 0.0001) amongst lymphoid (B cells and CD8 T cells) and blood-resident myeloid cells (dendritic cells, monocytes, neutrophils) suggesting stochastic activity of the Foxp3 promoter rather than developmental regulation in common ancestral progenitors. Interestingly, frequency of tdTomato+ dendritic cells, monocytes and neutrophils did not correlate with the tdTomato+ fraction in eosinophils, indicating that activity of the Foxp3 promoter in eosinophils occurred after the split from a common multipotent progenitor. When these F1 mice were crossed to achieve homozygosity of the promoter and reporter gene, a novel visually red phenotype was observed segregating amongst littermates. The red coloration was widespread and prevalent in non-immune tissues. Thymocytes examined from these red mice showed that all four subsets of immature thymocytes (CD4- CD8-) based on differential expression of CD25 and CD44 were expressing tdTomato. Finally, we show evidence of Foxp3 Cre recombinase independent tdTomato expression, suggesting germ line transmission of an activated tdTomato reporter gene. Our data highlights potential issues with conclusions drawn from using specifically the B6.129(Cg)-Foxp3tm4(YFP/Cre)Ayr/J mice.